Indigenous Resistance to Deforestation in Boven Digoel : The Awyu Tribe, Corporate Land Conversion, and UNDRIP Norm - Anissa Ramadhani (Dauliyah Journal of Islamic and International Affairs, 2026)
The indigenous Awyu tribe is currently resisting corporate-driven deforestation of its customary forests, which are central to the community’s livelihood and cultural identity. Large-scale forest clearance for oil palm plantations poses serious environmental risks, including the potential release of up to 25 million tons of carbon dioxide, with implications extending beyond Papua to the global climate. Deforestation also threatens the Awyu’s food security. It undermines spiritual practices that depend on continued access to customary lands, while increasing the risk of structural marginalisation as land conversion reshapes local power relations and weakens indigenous control over ancestral territories. This study aims to analyse the environmental damage associated with deforestation and examine how this ecological loss contributes to the cultural and social marginalisation of the Awyu tribe. Using a qualitative descriptive design, the research draws on secondary data from peer-reviewed journals, reports by environmental organisations, and relevant mass media sources. The analysis indicates that deforestation generates not only environmental degradation but also structural injustice, reflected in the erosion of indigenous rights, exclusion from decision-making processes, and disruption of customary livelihoods and cultural practices. The study, therefore, underscores the urgency of strengthening policies to protect indigenous peoples and safeguard customary forests from the expansion of extractive land use.